The unintended consequences of exemptions in conservation and management measures for fisheries management. (15th April 2023) - Haas, Bianca; Azmi, Kamal; Hanich, Quentin
Abstract: The duty to recognize the special requirements of developing states, and ensure that conservation and management measures avoid placing a disproportionate burden on them, has been firmly anchored in the United Nations Convention on the Law of the Sea and the United Nations Fish Stocks Agreement. Coastal developing states, particularly small island developing states (SIDS), are often economically and socially dependent on marine resources, and their development aspirations have been recognized by the international community. Ideally, members of regional fisheries management organizations (RFMOs) will meet their duty to avoid placing a disproportionate conservation burden on SIDS by designing and agreeing upon conservation and management measures that are equitable in terms of both their ease of implementation and their substantive impact on each participating state, such as through the equitable allocation of fishing opportunities. Where RFMOs are unable to adopt equitable measures, they may rely on the use of exemptions from conservation and management measures for developing states as a second-best alternative. However, exemptions have the potential to threaten the sustainability of the respective target stocks by creating loopholes in catch and effort limits. They can also undermine the scarcity value created by strong catch and effort limits, which can generate higher access fees for SIDS. In this paper, we analysed the conservation and management measures of RFMOs that include exemptions from catch, effort and capacity limits and found that they are used most commonly in the Western and Central Pacific Fisheries Commission. We argue that the use of exemptions due to the failure of RFMOs to adopt equitable allocation frameworks has the potential to negatively impact marine resources and their development opportunities. Instead, alternatives, such as equitable allocations of science-based catch and effort limits, transferability and phased adjustments, should be developed. Highlights: In fisheries management, the needs of developing countries need to be considered. To avoid disproportionate burdens, developing countries are exempt from some measures. Exemptions on catch and effort limits might negatively impact the fish stocks. It is important find alternatives to ensure equitable access to marine resources.